MACROMORPHOSCOPIC INVESTIGATION OF OSTEOARTHRITIS IN BRAZILIAN HUMAN SKELETONS: RELEVANT INFORMATION FOR FORENSIC ANTHROPOLOGY - Rendeiro, Sara Liz Medeiros (2024)
This research aimed to evaluate the occurrence of Osteoarthritis (OA) in human skeletons from an osteological collection in Northeastern Brazil, observing the most affected age and sex, as well as the bones most affected by the pathology. The research was conducted at the Centre for Forensic Anthropology Studies of the Faculty of Dentistry of the University of Pernambuco (CEAF/FOP/UPE), Recife, Brazil. Macroscopic examinations were performed on 123 skeletons of both sexes, aged at least 60 years. The presence of signs indicative of osteoarthritis was analyzed in bones of the lumbar vertebral region (lumbar vertebrae and lumbosacral joint), pelvic region (sacroiliac joint), and cervical region (vertebrae C2 to C7). It was observed that the lumbar vertebrae were the most affected by the pathology, with the lower faces more compromised. The mean age was 75.3 years, with a minimum age of 60 and a maximum of 109 years, with a higher occurrence in males. The most common degenerative change was porosity, followed by lipping, osteophytes, and eburnation.  Verifying the presence of this pathology and its characteristics can effectively contribute to forensic human identification, either by obtaining a biological profile in terms of estimating sex and age or as an individualization factor. Research such as this can help with information about the Brazilian population, which is extremely necessary for forensic anthropological practice in the country.